Kualitas Standar Pelayanan Publik Di Ruang Cempaka (Nifas Ponek) RSUD dr. Doris Sylvanus Palangka Raya - Puspita Sari; Rita Rahmaniati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This study aims to determine the Quality of Public Service Standards in Cempaka Room (Postpartum Ponek) RSUD dr. Doris Sylvanus. This research is a qualitative research with a naturalistic descriptive approach. Data collection is done by using interviews, observation, and documentation. Researchers Want to Describe How the Quality of Public Service Standards in Cempaka Room (Postpartum Ponek) RSUD dr. Doris Sylvanus, can work well with the community. The author uses 6 (Six) Public Service Standards, 1) Service Procedures, 2) Completion Time, 3) Service Costs, 4) Service Products, 5) Facilities and Infrastructure, 6) Competency of Service Providers. The results of research and interviews that have been conducted can be concluded that the Quality of Public Service Standards in Cempaka Room (Postpartum Ponek) RSUD dr. Doris Sylvanus still found several people who complained about the existing services, namely: (a) The completion time was not good enough in providing inpatient guarantee completion time, because the time of 3x24 hours was still felt to be too short for the recipient of services and the service flow was not yet one door so it needed long time in administrative management, (b) Facilities and service infrastructure contained in Cempaka Room (Postpartum Ponek) dr. Doris Sylvanus Palangka Raya which is still lack of medical aids so it is very difficult in providing health services. The author's suggestion to improve the quality and service in order to increase community satisfaction can be done by improving in terms of the existence of information boards on administrative service flow on the wall. The Hospital must procure new medical devices to support the quality of hospital health, increase maintenance of Hospital goods facilities and inadequate public facilities.